2017
DOI: 10.1093/icvts/ivx073
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning as a bridge to recovery from refractory hypoxaemia following lung transplantation†

Abstract: Prone positioning is safe and significantly improves gas exchange in patients with refractory hypoxaemia after lung transplantation. It should be considered as a possible treatment in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…6 The application of prone positioning has also been described as a rescue treatment to improve oxygenation in 22 lung transplantation recipients with refractory hypoxemia. 35 This is challenging to do in an acute postoperative patient, and further investigations are required to support its use in severe primary graft dysfunction.…”
Section: Review Articlementioning
confidence: 99%
“…6 The application of prone positioning has also been described as a rescue treatment to improve oxygenation in 22 lung transplantation recipients with refractory hypoxemia. 35 This is challenging to do in an acute postoperative patient, and further investigations are required to support its use in severe primary graft dysfunction.…”
Section: Review Articlementioning
confidence: 99%
“…P : F ratio was specifically reported in 7/11 studies 11–15,17,18 . None of these studies reported the conditions (FiO 2 and PEEP) under which the P : F ratio was determined nor any correlation with calculated shunt fraction.…”
Section: Resultsmentioning
confidence: 99%
“…During this process, patients may experience adverse events such as unplanned catheter removal, wound dehiscence, and wound bleeding, especially in the early stage after cardiothoracic surgery (17), and major thoracic surgery has been considered a contraindication for the prone position. However, a recent single-center nonrandomized trial showed that in the early stage after lung transplantation, the prone position was safe and could significantly improve gas exchange in patients with postoperative refractory hypoxemia (18), and the trial showed no complications by using prone positioning On postoperative day 7, the patient received airway clearance therapy with a high-frequency oscillator to increase the expiratory flow and improve the clearance rate of airway secretions. Esguerra-Gonzales et al (19) found that in patients after lung transplantation, airway clearance therapy 4 times a day helps improve peak expiratory flow, the dyspnea score, and oxygen saturation.…”
Section: Case Presentationmentioning
confidence: 99%